2017
DOI: 10.1111/jne.12452
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Kiss1r (Gpr54)‐Expressing Neurones in the Arcuate Nucleus of the Female Rat Hypothalamus

Abstract: Kisspeptin is essential in reproduction and acts by stimulating neurones expressing gonadotrophin-releasing hormone (GnRH). Recent studies suggest that kisspeptin has multiple roles in the modulation of neuronal circuits in systems outside the hypothalamic-pituitary-gonadal axis. Our recent research using in situ hybridisation (ISH) clarified the histological distribution of Kiss1r (Gpr54)-expressing neurones in the rat brain that were presumed to be putative targets of kisspeptin. The arcuate nucleus (ARN) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
(65 reference statements)
0
27
0
Order By: Relevance
“…Chronic Kp10 increased Pomc and Npy in males, but not in females, which could explain why only male hamsters modified their metabolic phenotype. POMC neurones receive a dense Kp innervation and express Kiss1r in rats, they are directly activated by Kp in mice and they are regulated by a central Kp10 injection in jerboas, altogether supporting a direct effect of Kp on POMC neurones. On the other hand, castration completely abolished the effect of Kp10 on body weight and, because testosterone is known to regulate Pomc and Npy, probably also part of the Kp effect on the metabolic genes is testosterone‐dependent.…”
Section: Discussionmentioning
confidence: 90%
“…Chronic Kp10 increased Pomc and Npy in males, but not in females, which could explain why only male hamsters modified their metabolic phenotype. POMC neurones receive a dense Kp innervation and express Kiss1r in rats, they are directly activated by Kp in mice and they are regulated by a central Kp10 injection in jerboas, altogether supporting a direct effect of Kp on POMC neurones. On the other hand, castration completely abolished the effect of Kp10 on body weight and, because testosterone is known to regulate Pomc and Npy, probably also part of the Kp effect on the metabolic genes is testosterone‐dependent.…”
Section: Discussionmentioning
confidence: 90%
“…122 We have further investigated this question using whole-cell patch clamp recordings in juvenile male rats, and we found no direct effect of kisspeptin-10 on the electrical activity of TIDA neurons. Similarly, others have reported that only a few TIDA neurons express Kiss1r in the female rat, 126 suggesting that Kiss1r does not play a significant role in this neuronal population.…”
Section: Kiss1r and Alternative Pathways For The Kisspeptin Effect Onmentioning
confidence: 82%
“…Thus, it is speculated that calcitonin and/or amylin could affect the tubuloinfundibular dopaminergic (TIDA) neurons, which in turn, might contribute to controlling prolactin release from the anterior pituitary during lactation. Interestingly, GPR54 expression was evident in the TIDA neurons in rats, suggesting that ARC kisspeptin and TIDA neurons could interact with each other through kisspeptin and CALCR signaling. Furthermore, the Calcr‐ expressing cells in the brain regions close to the cerebral ventricles might have a role as an interface of peripheral and central interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GPR54 expression was evident in the TIDA neurons in rats, 43 suggesting that ARC kisspeptin and TIDA neurons could interact with each other through kisspeptin and CALCR signaling.…”
Section: Colocalizationofcalcrandkiss1expression Inthearcuatenucleumentioning
confidence: 99%